2018
DOI: 10.1021/acs.jpcc.7b11026
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Encapsulation and Release of Substances Based on Temperature and Photoresponsive Nanocapsules

Abstract: In this study, dual-responsive polymeric nanocapsules, in which the state (swelling or collapse) can be repeatedly controlled by external stimuli (i.e., temperature and light), have been designed and prepared through distillation–precipitation polymerization. Temperature sensitive monomers of N-isopropylacrylamide are cross-linked by photoresponsive bis­(methacryloylamino) onto a silica nanospherical template to form a core–shell (SiO2–PNIPAM/Azo) structure. The silica core is then removed by hydrofluoric acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The peak at 2900cm − 1 corresponding to the C-H stretching vibration of -CH 3 in CTAB disappeared in the spectrum of SiO 2 -TSUA showing the successful removal of the surfactant [28,29]. Compared to the spectra of TUSA, the characteristic bands at 1550cm − 1 and 3060cm − 1 corresponding to N = N and C-H of azobenzene groups in the spectrum of SiO 2 -TSUA indicated that the TSUA had grafted onto silica successfully [30]. Meanwhile the broad peak at around 3447cm − 1 in the spectrum of SiO 2 corresponding to stretching vibration of O-H shifted to 3350cm − 1 in the spectra of SiO 2 -TSUA indicating that the amino groups were successfully incorporated in silica.…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 2900cm − 1 corresponding to the C-H stretching vibration of -CH 3 in CTAB disappeared in the spectrum of SiO 2 -TSUA showing the successful removal of the surfactant [28,29]. Compared to the spectra of TUSA, the characteristic bands at 1550cm − 1 and 3060cm − 1 corresponding to N = N and C-H of azobenzene groups in the spectrum of SiO 2 -TSUA indicated that the TSUA had grafted onto silica successfully [30]. Meanwhile the broad peak at around 3447cm − 1 in the spectrum of SiO 2 corresponding to stretching vibration of O-H shifted to 3350cm − 1 in the spectra of SiO 2 -TSUA indicating that the amino groups were successfully incorporated in silica.…”
Section: Resultsmentioning
confidence: 99%
“…Because the azo groups are inhibited to the radical chain reaction by the azo group, it is difficult to form pure azo chromophore particles through emulsion . Our group have successfully obtained photoresponsive polyazobenzene particles by using the distillation precipitation polymerization . When the solvent is distilled at a constant rate, a high monomer conversion could be maintained and a lower monomer concentration at the start of the reaction can prevent the particles from aggregating .…”
Section: Resultsmentioning
confidence: 99%
“…4,4′-Diaminoazobenzene (DAAB) was synthesized according to the ref . BMAAB was prepared using a temperature dehydration reaction.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Similar phenomena in which the external conditions affected the diffusion coefficient were observed. 23,45 Furthermore, the accuracy can be further improved by conjugating targeted biomolecules (e.g., folic acid, transferrin, and monoclonal antibodies) on the nanocapsule surface through the free carboxyl groups (i.e., carbodiimide chemistry). This work successfully demonstrated a yolk−shell structured drug delivery system with pH-and NIR-responsive features.…”
Section: Resultsmentioning
confidence: 99%